Dietary vitamin A regulates wingless-related MMTV integration site signaling to alter the hair cycle. (May 2015) - Suo, Liye; Sundberg, John P; Everts, Helen B
Alopecia areata (AA) is an autoimmune hair loss disease caused by a cell-mediated immune attack of the lower portion of the cycling hair follicle. Feeding mice 3–7 times the recommended level of dietary vitamin A accelerated the progression of AA in the graft-induced C3H/HeJ mouse model of AA. In this study, we also found that dietary vitamin A, in a dose dependent manner, activated the hair follicle stem cells (SCs) to induce the development and growth phase of the hair cycle (anagen), which may have made the hair follicle more susceptible to autoimmune attack. Our purpose here is to determine the mechanism by which dietary vitamin A regulates the hair cycle. We found that vitamin A in a dose-dependent manner increased nuclear localized beta-catenin (CTNNB1; a marker of canonical wingless-type Mouse Mammary Tumor Virus integration site family (WNT) signaling) and levels of WNT7A within the hair follicle bulge in these C3H/HeJ mice. These findings suggest that feeding mice high levels of dietary vitamin A increases WNT signaling to activate hair follicle SCs.